Numerical analysis of baffles on geothermal energy in a U-shaped heat exchanger - Lamia Benahmed; Khaled Aliane; Brahim Rostane; Said Abboudi (Renewable Energy and Sustainable Development, 2025)
This work focuses on geothermal energy recovery using a vertical geothermal heat exchanger coupled with a heat pump for heating applications. The primary objective of this study is to conduct a 3D numerical simulation to evaluate the effects of baffles on the thermal performance of a U-shaped heat exchanger. These baffles, designed to alter flow characteristics, were implemented to enhance heat transfer and optimize overall system efficiency. The mathematical model is based on the governing equations of fluid mechanics and thermodynamics, solved using the finite volume method in the Ansys CFX software. Various baffle configurations were investigated, focusing on their placement (on the inlet and outlet tube), geometry, and the use of perforations with decreasing diameters. Simulations were conducted for a Reynolds number of Re=3600, capturing the flow behavior under specific conditions. The analysis revealed that the optimal configuration, involving baffles strategically placed on the outlet tube with decreasing perforation diameters, significantly improved thermal performance. These findings highlight the potential for designing more efficient heat exchangers in geothermal systems, paving the way for advancements in sustainable energy solutions.